Inflammasome Activation Induced by Perfringolysin O of Clostridium perfringens and Its Involvement in the Progression of Gas Gangrene - Yamamura, Kiyonobu; Ashida, Hiroshi; Okano, Tokuju; Kinoshita-Daitoku, Ryo; Suzuki, Shiho; Ohtani, Kaori; Hamagaki, Miwako; Ikeda, Tohru; Suzuki, Toshihiko (Frontiers in Microbiology, 2019)
Clostridium perfringens (C. perfringens) is Gram-positive anaerobic, spore-forming rod-shaped bacterial pathogen that is widely distributed in nature. This bacterium is known as the causative agent of a foodborne illness and of gas gangrene. While the major virulence factors are the alpha-toxin and perfringolysin O (PFO) produced by type A strains of C. perfringens, the precise mechanisms of how these toxins induce the development of gas gangrene are still not well understood. In this study, we analyzed the host responses to these toxins, including inflammasome activation, using mouse bone marrow-derived macrophages (BMDMs). Our results demonstrated, for the first time, that C. perfringens triggers the activation of caspase-1 and release of IL-1β through PFO-mediated inflammasome activation via a receptor of the Nod-like receptor (NLR) family, pyrin-domain containing 3 protein (NLRP3). The PFO-mediated inflammasome activation was not induced in the cultured myocytes. We further analyzed the functional roles of the toxins in inducing myonecrosis in a mouse model of gas gangrene. Although the myonecrosis was found to be largely dependent on the alpha-toxin, PFO also induced myonecrosis to a lesser extent, again through the mediation of NLRP3. These results suggest that C. perfringens triggers inflammatory responses via PFO-mediated inflammasome activation via NLRP3, and that this axis contributes in part to the progression of gas gangrene. Our findings provide a novel insight into the molecular mechanisms underlying the pathogenesis of gas gangrene caused by C. perfringens.